Pengaruh Corporate Social Responsibility, Employee Engagement, dan Pengembangan Karir Terhadap Kinerja Karyawan di PT Aerofood Indonesia Unit Surabaya (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of Corporate Social Responsibility (CSR), Employee Engagement, and Career Development on employee performance at PT Aerofood Indonesia Unit Surabaya. The study used a quantitative approach with a sample of 85 employees selected using random sampling techniques. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with the help of IBM SPSS Statistics. The results of the study indicate that paSrtially only Employee Engagement has a significant effect on employee performance, while Corporate Social Responsibility and Career Development have no significant effect. However, simultaneously all three variables have a significant effect on employee performance. This finding indicates that employee engagement is the most influential factor in improving performance. The research model is able to explain 36.7% of the variation in employee performance, while the rest is influenced by other factors outside the study. Therefore, companies need to strengthen strategies to increase employee engagement and optimize the implementation of CSR and career development programs to support sustainable performance improvement.